Reading EEGs a practical approach - Greenfield, L. John, Jr; Geyer, James D.; Carney, Paul R. (Wolters Kluwer, 2021)
"Reading EEGs: A Practical Approach focuses on pattern recognition and pattern comparison. The concepts of pattern recognition are developed in a logical fashion based on appearance rather than disease process. The book teaches waveform recognition so that the reader can generate a differential diagnosis based on that recognition. This book also incorporates a question-and-answer format that is effective for students at multiple levels of training"--